Mogamulizumab-induced vitiligo: 3 cases. (October 2021) - De Masson, Adele; Algarni, Abdullah; Ram-Wolff, Caroline; Bagot, Martine; Battistella, Maxime; Vignon, Dominique
Abstract : Background: Mogamulizumab is a novel defucosylated monoclonal antibody targeting C-C chemokine receptor 4 (CCR4) that eradicates Sézary cells via antibody-dependent cellular cytotoxicity. Treatment of Sézary syndrome with mogamulizumab has recently shown an increase in progression-free survival compared to vorinostat in previously treated cutaneous T-cell lymphoma. Objectives: To investigate immune side effects of mogamulizumab in Sézary syndrome patients. Materials and methods: Three cases of Sézary syndrome patients treated with mogamulizumab who developed clinically confirmed vitiligo were reported. Results: Case 1 was a 66-year-old woman from Tunisia. Seven months after the administration of mogamulizumab, she developed vitiligo on her face and hands while still in complete remission of Sézary syndrome. Case 2 was a 72-year-old woman from Martinique, with no history of autoimmune disease, who was diagnosed with stage IVA1 Sézary syndrome. The patient received multiple lines of treatment with no improvement. After six months of mogamulizumab treatment, while still on treatment, the patient progressively developed well-demarcated depigmented patches on the scalp, upper limbs, and trunk, consistent with vitiligo. Case 3 was a 38-year-old woman from France, who was diagnosed with Sézary syndrome in October 2019. Mogamulizumab therapy was started in December 2019. Eight months later, she developed histologically confirmed vitiligo on her legs. Conclusions: Vitiligo can be another autoimmune manifestation associated with mogamulizumab, and the occurrence of vitiligo could be a favorable predictive factor for response to treatment.